The mitochondrial functional characteristics and microstructure play an important role in yak meat color during wet curing - Zhuo Wang; Jibing Ma; Guoyuan Ma; Qunli Yu; Ling Han; Li Zhang (Food Chemistry: X)
The study investigated the impact of low-dose sodium nitrite on yak meat color and mitochondrial functional characteristics during the wet curing. The results showed that sodium nitrite significantly enhanced the redness (a⁎ value) of yak meat by increasing the activities of mitochondrial complexes I, II, III and IV, which are critical for electron transport and aerobic respiration. Additionally, sodium nitrite reduced mitochondrial swelling and membrane permeability, and slowed the production of lipid oxidation products, indicating protective effects against mitochondrial damage and preserving mitochondrial integrity. Correlation analysis and Orthogonal Partial Least Squares Discriminant Analysis (OPLS-DA) identified mitochondrial complex I activity, NADH-dependent metmyoglobin reductase activity, and specific lipid oxidation products as key factors influencing the a⁎ value of yak meat. These findings highlighted the significant role of mitochondrial function and structure in meat color stability.